Microbial Antigens Stimulate Metalloprotease-7 Secretion in Human B-Lymphocytes Using mTOR-Dependent and Independent Pathways - Mohamed F. Ali (Nature Portfolio, 2017)
Abstract Metalloproteinases (MMPs) contribute to tissue remodeling and acute inflammation not only by degrading extracellular matrix proteins but also by controlling the influx of chemokines through the regulation and shedding of syndecans. B-lymphocytes, in addition to their well-known function as antibody producing cells, participate in the innate immune response by secreting inflammatory cytokines and chemokines. However, there is little information about the role of B-lymphocytes in the regulation of MMPs; consequently, herein we investigated whether activated human circulating B-lymphocytes contributed to the secretion of MMPs. We demonstrate that B-lymphocytes activated by un-methylated CpG motifs, found in bacterial DNA, and β-glucans, found in the cell wall of fungi, both induced MMP-7. Interestingly, while CpG-stimulated cells activated the mTOR pathway via TLR9 receptor to induced MMP-7, β-glucan-stimulated cells were mTOR-independent and used Dectin-1 receptor. B-lymphocytes did not seem to have a major role in the secretion of tissue inhibitors of metalloproteinases (TIMPs). However, secreted MMP-7 participated in the shedding of Syndecan-4 from the surface of B-lymphocytes. In conclusion, circulating human B-lymphocytes contribute to the regulation of the innate immune system by participating in the secretion of MMP-7 which in turn is important for the shedding of Syndecan-4 in response to infectious stimuli.